The SET Domain Protein, Set3p, Promotes the Reliable Execution of Cytokinesis in Schizosaccharomyces pombe - Rentas, Stefan; Saberianfar, Reza; Grewal, Charnpal; Kanippayoor, Rachelle; Mishra, Mithilesh; McCollum, Dannel; Karagiannis, Jim (PLOS ONE, 2012)
In response to perturbation of the cell division machinery fission yeast cells activate regulatory networks that ensure the faithful completion of cytokinesis. For instance, when cells are treated with drugs that impede constriction of the actomyosin ring (low doses of Latrunculin A, for example) these networks ensure that cytokinesis is complete before progression into the subsequent mitosis. Here, we identify three previously uncharacterized genes, hif2, set3, and snt1, whose deletion results in hyper-sensitivity to LatA treatment and in increased rates of cytokinesis failure. Interestingly, these genes are orthologous to TBL1X, MLL5, and NCOR2, human genes that encode components of a histone deacetylase complex with a known role in cytokinesis. Through co-immunoprecipitation experiments, localization studies, and phenotypic analysis of gene deletion mutants, we provide evidence for an orthologous complex in fission yeast. Furthermore, in light of the putative role of the complex in chromatin modification, together with our results demonstrating an increase in Set3p levels upon Latrunculin A treatment, global gene expression profiles were generated. While this analysis demonstrated that the expression of cytokinesis genes was not significantly affected in set3Δ backgrounds, it did reveal defects in the ability of the mutant to regulate genes with roles in the cellular response to stress. Taken together, these findings support the existence of a conserved, multi-protein complex with a role in promoting the successful completion of cytokinesis.